2013
DOI: 10.1177/0300985813480216
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune System of the Perinatal Lung and Responses to Respiratory Syncytial Virus Infection

Abstract: The response of the preterm and newborn lung to airborne pathogens, particles, and other insults is initially dependent on innate immune responses since adaptive responses may not fully mature and require weeks for sufficient responses to antigenic stimuli. Foreign material and microbial agents trigger soluble, cell surface, and cytoplasmic receptors that activate signaling cascades that invoke release of surfactant proteins, defensins, interferons, lactoferrin, oxidative products, and other innate immune subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 145 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…As rodents are only semi-permissive to infection with human RSV, we tested the therapeutic efficacy of JNJ-53718678 and of a highly active, structurally and mechanistically close analog with similar oral PK, JNJ-49214698, in a fully replicative neonatal lamb disease model of RSV (Supplementary Table 8 ) 34 . Neonatal lambs have similar pulmonary structure, as compared to humans 40 they develop similar clinical symptoms as infants upon infection with RSV, innate and adaptive immune responses by neonatal lambs closely parallel those of infants 39 , 41 , and histological lesions in the bronchioles are characterized by epithelial injury, neutrophil infiltration, and syncytial cell formation, all hallmarks of RSV-induced microscopic lung lesions in humans 43 . When animals with an established RSV ALRTI received oral, once-daily treatment starting 1 day after infection with doses of either 1, 5, or 25 mg kg −1 JNJ-53718678, a dose-dependent decrease of RSV infectious titer was present on Day 6 after infection in BALF and lavaged-lung tissue, resulting in an (almost) complete eradication of the RSV infectious titer in both compartments of the lung (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As rodents are only semi-permissive to infection with human RSV, we tested the therapeutic efficacy of JNJ-53718678 and of a highly active, structurally and mechanistically close analog with similar oral PK, JNJ-49214698, in a fully replicative neonatal lamb disease model of RSV (Supplementary Table 8 ) 34 . Neonatal lambs have similar pulmonary structure, as compared to humans 40 they develop similar clinical symptoms as infants upon infection with RSV, innate and adaptive immune responses by neonatal lambs closely parallel those of infants 39 , 41 , and histological lesions in the bronchioles are characterized by epithelial injury, neutrophil infiltration, and syncytial cell formation, all hallmarks of RSV-induced microscopic lung lesions in humans 43 . When animals with an established RSV ALRTI received oral, once-daily treatment starting 1 day after infection with doses of either 1, 5, or 25 mg kg −1 JNJ-53718678, a dose-dependent decrease of RSV infectious titer was present on Day 6 after infection in BALF and lavaged-lung tissue, resulting in an (almost) complete eradication of the RSV infectious titer in both compartments of the lung (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Until then, modeling disease impact of antivirals in animal RSV-infection models remains an important strategy for drug developers to guide decision making related to which compounds to select as candidates for clinical development. Neonatal lambs were recently described as a fully permissive model for RSV disease, with a high similarity to infants concerning lung physiology, viral replication, and virus-induced lung pathology 39 41 . In these animals, internal signs of RSV-induced ALRTI can be detected by auscultation as soon as 24 h post infection of the lungs, while 3 days after infection, viral lung titer in the animals is close to peak and, concomitantly, the lambs display clear external symptoms of RSV disease in the lower respiratory tract 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial proteins are a first line of defense at barrier sites and are produced primarily by epithelial cells and innate leukocytes, particularly neutrophils (97,98). In the lung, they include surfactants as well as S100s, β-defensins, and cathelicidin and they may provide protection against important infant respiratory infections, including RSV (99)(100)(101)(102). Cathelicidin has direct antiviral activity against RSV, can prevent infection in vitro and in vivo and in children hospitalized with bronchiolitis, those with low serum cathelicidin were significantly more likely to have RSV infection and a longer hospital stay (97,(103)(104)(105)(106)(107).…”
Section: Respiratory Epithelial Cellsmentioning
confidence: 99%
“…PM 2.5 exposure can increase the risk of respiratory viral infections (Wang et al, 2003 ). Surfactant protein A (SP-A) and clara cell secretory protein (CCSP) are both important components of innate immune defense mediators for antiviral respiratory infection (Wang et al, 2003 ; Derscheid and Ackermann, 2013 ). Harrod et al found that DEP-exposed mice have significantly higher gene expression of RSV in lung tissues than control mice (Wang et al, 2003 ).…”
Section: Pm 25 and Airway Inflammation In Copdmentioning
confidence: 99%